A Post Hoc Analysis of Osmotherapy Use in the Erythropoietin in Traumatic Brain Injury Study—Associations With Acute Kidney Injury and Mortality - Skrifvars, Markus B. (Crit Care Med, 2021)
Mannitol and hypertonic saline are used to treat raised intracerebral pressure in patients with traumatic brain injury, but their possible effects on kidney function and mortality are unknown. DESIGN: A post hoc analysis of the erythropoietin trial in traumatic brain injury (ClinicalTrials.gov NCT00987454) including daily data on mannitol and hypertonic saline use. SETTING: Twenty-nine university-affiliated teaching hospitals in seven countries. PATIENTS: A total of 568 patients treated in the ICU for 48 hours without acute kidney injury of whom 43 (7%) received mannitol and 170 (29%) hypertonic saline. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We categorized acute kidney injury stage according to the Kidney Disease Improving Global Outcome classification and defined acute kidney injury as any Kidney Disease Improving Global Outcome stage-based changes from the admission creatinine. We tested associations between early (first 2 d) mannitol and hypertonic saline and time to acute kidney injury up to ICU discharge and death up to 180 days with Cox regression analysis. Subsequently, acute kidney injury developed more often in patients receiving mannitol (35% vs 10%; p < 0.001) and hypertonic saline (23% vs 10%; p < 0.001). On competing risk analysis including factors associated with acute kidney injury, mannitol (hazard ratio, 2.3; 95% CI, 1.2–4.3; p = 0.01), but not hypertonic saline (hazard ratio, 1.6; 95% CI, 0.9–2.8; p = 0.08), was independently associated with time to acute kidney injury. In a Cox model for predicting time to death, both the use of mannitol (hazard ratio, 2.1; 95% CI, 1.1–4.1; p = 0.03) and hypertonic saline (hazard ratio, 1.8; 95% CI, 1.02–3.2; p = 0.04) were associated with time to death. CONCLUSIONS: In this post hoc analysis of a randomized controlled trial, the early use of mannitol, but not hypertonic saline, was independently associated with an increase in acute kidney injury. Our findings suggest the need to further evaluate the use and choice of osmotherapy in traumatic brain injury.